Pelatihan Penggunaan Aplikasi Sistem Informasi Gender dan Anak Tingkat Kota Kendari Tahun 2023 - Arbiansyah; La Ode Hartono; Ikhuzain Maftuh Aksa; Faldi saputra; Darman, Darman (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The use of information and communication technology (ICT) in the world has become increasingly widespread. This can be seen from the use of ICT which is not limited to the trade sector, but also in other fields, such as education, defense and state security, social and so on. ICT is used because it has advantages compared to using traditional methods of interaction. The advantages of ICT are speed, convenience, lower costs, data centralization and data access that can be used by all groups. With the advantages as above, it can be said that using ICT can create efficiency in the movement of human life in interacting with each other. Therefore, ICT is widely applied in various fields of human life, and with the advantages offered by this technology, it is starting to be applied in government practice. The development of technology and information sources from all media, it turns out that internet media is currently very popular with the public and business people. The information obtained is fast and accurate and can also be used and obtained anywhere. The use of technology and information is increasingly wider in scope, including in government management. Implementing E-Government is also a necessity in responding to challenges in the current Information Technology Era. One of them is by developing a website that can increase information disclosure. By implementing a website, it can help provide information and as a means to reach the public, which of course can help the performance of the Kendari City Women's Empowerment and Child Protection Service (DPPPA) to improve services to the community.